Kecemasan masa depan dan sikap mahasiswa terhadap jurusan akademik - Firanda Putri Maharani; Diah Karmiyati; Dian Caesaria Widyasari (Fakultas Psikologi, 2021)
It is often found that students feel they are in the wrong major which leads to feeling confused about choosing their future career. As a result, students think they cannot choose a career that suits their major and end up feeling anxious about their future. This study aims to determine the relationship between future anxiety and student attitudes towards academic majors. This correlational quantitative research involved 150 samples based on purposive sampling with characteristics as active students in university located in East Java, female or male aged 18-25 years. The instruments used were Future Anxiety Scale for future anxiety variables and Attitude toward Specialization Scale for attitude toward academic majors. Based on the Pearson correlation product moment test showed that there was a positive relationship between future anxiety and student attitudes towards academic majors (r = 0,326, p < 0.001) with contribution of 10.6%. The higher the level of future anxiety of students, the more positive student’s attitude towards their academic majors. Implications that refer to the results of this research for students who are feeling anxious about the future so they can respond to their academic majors positively.